2022
DOI: 10.1128/msystems.01450-21
|View full text |Cite
|
Sign up to set email alerts
|

Meet Me in the Middle: Median Temperatures Impact Cyanobacteria and Photoautotrophy in Eruptive Yellowstone Hot Springs

Abstract: Hot spring cyanobacteria have long been model systems for examining ecological diversification as well as characterizing microbial adaptation and evolution to extreme environments. These studies have reported cyanobacterial diversification in hot spring outflow channels that can be defined by distinct temperature ranges.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…a genetically cohesive population that occupies a slightly different ecological niche as its ancestor ( 54 )), can be generated and maintained in hot spring environments that have partially overlapping niches, either temporally or spatially ( 55–59 ). In hot springs, such ecotype variation has been observed among Synechococcus strains that have different temperature optima and/or light absorbance properties, allowing for their stable coexistence ( 55–57 , 60 ). Consequently, it is possible that the temporal dynamics of OFG and SG, in particular the splash pool of OFG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…a genetically cohesive population that occupies a slightly different ecological niche as its ancestor ( 54 )), can be generated and maintained in hot spring environments that have partially overlapping niches, either temporally or spatially ( 55–59 ). In hot springs, such ecotype variation has been observed among Synechococcus strains that have different temperature optima and/or light absorbance properties, allowing for their stable coexistence ( 55–57 , 60 ). Consequently, it is possible that the temporal dynamics of OFG and SG, in particular the splash pool of OFG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The limits of thermophily in circum-neutral pH hot springs for the Cyanobacteria and Chloroflexota are well-established from numerous studies in various regions, e.g., Nakagawa and Fukui (2002), Lau et al (2006), Miller et al (2009), and Podar et al (2020. A recent study has also identified the potential influence of thermal fluctuation on cyanobacterial fitness in hot springs (Hamilton and Havig, 2022). Both the Cyanobacteria and Chloroflexia also include known sulfide-tolerant ecotypes and this must also be viewed as an adaptive advantage in hot springs where sulfide is a common stressor: Sulfide is generally toxic to cyanobacterial primary metabolism because it inhibits cytochrome c oxidase and irreversibly affects the oxygen binding center in photosystem II (Miller and Bebout, 2004).…”
Section: Adaptation Of Phototrophic Bacteria To Hot Springsmentioning
confidence: 96%
“…Although the biogeographic and speciation issues of thermophilic cyanobacteria are of extraordinary interest, they have been the focus of only a minority of modern studies [15,16]. Understandably, species surviving the highest temperatures, such as "Synechococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Understandably, species surviving the highest temperatures, such as "Synechococcus sp. ", have received the most attention [8][9][10][14][15][16]. Studies on simple filamentous cyanobacteria (usually referred to as Leptolyngbya spp.)…”
Section: Introductionmentioning
confidence: 99%